Graphene-based protein biomarker detection - Patil, Amol V.; Fernandes, Flávio Bedatty [UNESP]; Bueno, Paulo Roberto [UNESP]; Davis, Jason John (Future Sci Ltd, 2015)
An ability to detect and quantify protein molecules, harbingers of specific pathologies, potentially underpins both early disease diagnosis and an assessment of treatment efficacy. However, the specific detection of a particular protein biomarker in a complex environment is by no means an easy task and requires a progressive improvement in sensor technology. The high surface area, volume, electrical conductance, atomic level thickness and apparent biocompatibility of graphene makes it potentially an exceedingly powerful transducer of biorecognition events; the demands of its application in biosensing, and progress to date are reviewed herein.